1979
DOI: 10.1017/s0025315400042612
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme variation inChthamalus stellatusandChthamalus montagui(Crustacea: Cirripedia): evidence for the presence ofC. montaguiin the Adriatic

Abstract: The electrophoretic mobilities of 13 enzymes in two species of Chthamalus, C. stellatus Poli and C. montagui Southward, were compared. These species differed absolutely for eight of the enzymes and exhibited some species-specific allozymes for a further four enzymes. No evidence of hybridization was found. The observed mean heterozygosity was 0087 for C. stellatus and 0179 for C. montagui.A sample of ‘C. montagui’ from Venice differed from two samples from south-west England in external shell characters and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
(25 reference statements)
4
27
0
Order By: Relevance
“…The primers developed during the course of this study will also successfully amplify DNA from several other species of acorn barnacles. Previous work on the genetic profiles of C. stellatus and C. montagui focussed on different enzyme allozyme frequencies as an aid in their separation as adults (Dando et al 1979) and newly metamorphosed individuals (Burrows 1988 Sizes of genetically-identified cyprids collected at Garrettstown, southwest Ireland on the genetic variation within C. montagui (Dando & Southward 1980, Pannacciulli et al 1997) and C. stellatus populations (Pannacciulli et al 1997) have also used allozymes. A previous suggestion that size could be used as a tool to distinguish these species, was based on bimodally distributed carapace length data from August 1996 ) and comparisons of these lengths with laboratory-reared Chthamalus stellatus (Al-Yahya 1991) and C. montagui cypnds (Burrows 1988, Stone 1989, WhiUis et al 1990, Al-Yahya 1991, O'Riordan 1992, Jensen et al 1994, Moyse et al 1995.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers developed during the course of this study will also successfully amplify DNA from several other species of acorn barnacles. Previous work on the genetic profiles of C. stellatus and C. montagui focussed on different enzyme allozyme frequencies as an aid in their separation as adults (Dando et al 1979) and newly metamorphosed individuals (Burrows 1988 Sizes of genetically-identified cyprids collected at Garrettstown, southwest Ireland on the genetic variation within C. montagui (Dando & Southward 1980, Pannacciulli et al 1997) and C. stellatus populations (Pannacciulli et al 1997) have also used allozymes. A previous suggestion that size could be used as a tool to distinguish these species, was based on bimodally distributed carapace length data from August 1996 ) and comparisons of these lengths with laboratory-reared Chthamalus stellatus (Al-Yahya 1991) and C. montagui cypnds (Burrows 1988, Stone 1989, WhiUis et al 1990, Al-Yahya 1991, O'Riordan 1992, Jensen et al 1994, Moyse et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial and temporal variation in the sizes of field-collected cyprids of C. stellatus and C, montagui are currently being investigated from a number of European sites . Species of Chthamalus are frequently sympatric over part of their range (Southward 1976, Dando et al 1979, Dando & Southward 1980 but studies on the settlement phase of sympatric C. stellatus and C , montagui population~ are dependent upon a diagnostic tool such as carapace length to reliably and q.uickly identify large numbers of cyprids from field samples along the species ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the most comprehensive distribution of these species in the northeast Atlantic, the Mediterranean, and the Black Sea was presented by Pannacciulli et al (1997). Dando et al (1979) compared the differences among populations of C. stellatus and C. montagui from the Adriatic and southwest England and found that C. montagui from the Adriatic differed from the English population, whereas C. stellatus from all sites had similar allele frequencies. Slight variations in the allozyme frequencies of the glutamate oxaloacetate transaminase (GOT) locus of C. stellatus were later reported (Pannacciulli et al 1997), suggesting genetic differences between the Atlantic and the Mediterranean populations.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore compared Hawaiian material with several other species, both by conventional morphology and by allozyme electrophoresis. Previous investigations of Chthamalus species have shown the value of allozyme coniparisons, not only in separating subgenera and species but also in pointing out possible varietal differences (Dando et al 1979, Hedgecock 1979, Dando & Southward 1980, 1981, Miller et al 1989). The Hawaiian specimens were externally unlike typical Chthamalus species from the Pacific coast of Amer- Southern and Central California and its southern allies, including C. panaa book on the marine fauna for Hawaii), in Pearl Harbor (by S.L.C.…”
Section: Introductionmentioning
confidence: 99%